Antivirulence effects of cell-free culture supernatant of endophytic bacteria against grapevine crown gall agent, Agrobacterium tumefaciens, and induction of defense responses in plantlets via intact bacterial cells - Faegheh Etminani; Behrouz Harighi; Bahman Bahramnejad; Ali Akbar Mozafari (BMC Plant Biology, 2024)
Abstract Background Crown gall disease caused by Agrobacterium tumefaciens is a very destructive affliction that affects grapevines. Endophytic bacteria have been discovered to control plant diseases via the use of several mechanisms. This research examined the potential for controlling crown gall by three endophytic bacteria that were previously isolated from healthy cultivated and wild grapevines including Pseudomonas kilonensis Ba35, Pseudomonas chlororaphis Ba47, and Serratia liquefaciens Ou55. Result At various degrees, three endophytic bacteria suppressed the populations of A. tumefaciens Gh1 and greatly decreased the symptoms of crown gall. Furthermore, biofilm production and motility behaviors of A. tumefaciens Gh1were greatly inhibited by the Cell-free Culture Supernatant (CFCS) of endophytic bacteria. According to our findings, CFCS may reduce the adhesion of A. tumefaciens Gh1 cells to grapevine cv. Rashe root tissues as well as their chemotaxis motility toward the extract of the roots. When compared to the untreated control, statistical analysis showed that CFCS significantly reduced the swimming, twitching, and swarming motility of A. tumefaciens Gh1. The findings demonstrated that the endophytic bacteria effectively stimulated the production of plant defensive enzymes including superoxide dismutase (SOD), polyphenol oxidase (PPO), peroxidase (POD), phenylalanine ammonia lyase (PAL), and total soluble phenols at different time intervals in grapevine inoculated with A. tumefaciens Gh1. The Ba47 strain markedly increased the expression levels of defense genes associated with plant resistance. The up-regulation of PR1, PR2, VvACO1, and GAD1 genes in grapevine leaves indicates the activation of SA and JA pathways, which play a role in enhancing resistance to pathogen invasion. The results showed that treating grapevine with Ba47 increased antioxidant defense activities and defense-related gene expression, which reduced oxidative damage caused by A. tumefaciens and decreased the incidence of crown gall disease. Conclusion This is the first study on how A. tumefaciens, the grapevine crown gall agent, is affected by CFCS generated by endophytic bacteria in terms of growth and virulence features. To create safer plant disease management techniques, knowledge of the biocontrol processes mediated by CFCS during microbial interactions is crucial.